The cushioning effect of immigrant mobility - Özgüzel, Cem (CESifo, Center for Economic Studies & Ifo Institute, 2021)
During the Great Recession, immigrants reacted to the drop in labour demand in Spain through internal migration or leaving the country. Consequently, provinces lost 13.5% of their immigrants or - 3% of the total labour supply, on average. Using municipal registers and longitudinal administrative data, I find that immigrant outflows slowed the decline in employment and wage of natives. I use a modified shift-share instrument based on past settlements to claim causality. Employment effects were driven by increased entries to employment, while wage effects were limited to natives that were already employed. These effects also persisted in the medium-term.
10419/245449
Keywords: Graue Literatur; immigrant mobility; wages; employment; local labour market; Great Recession; Spain